Pseudomonas Pseudoalcaligenes Caused Otogenic Cerebellar Brain Abscess In Indonesian Child - Prastiya Indra Gunawan; Achmad Chusnu Romdhoni (Indian Journal of Forensic Medicine & Toxicology, 2021)
Otogenic brain abscess is a common intracranial complication from chronic supurative otitis media.Pseudomonas pseudoalcaligenes is a rare cause of brain abscess. Prompt diagnosis and decision making issignificant in order to decrease the mortality rate from this type of abscess. We described A 13-year-old boypresented with decreased consciousness, positive meningeal signs, and pathological reflexes. There was ahistory of chronic suppurative otitis media. A head CT scan revealed multiple left cerebellar abscesses andbrain edema. The abscess wall culture revealed P. pseudoalcaligenes. After being managed with surgicalabscess drainage, mastoidectomy, ear flushing, and antimicrobial therapy for six weeks, his consciousnesslevel improved. Cerebellar neurological impairment was still observed. Physical and neurologicalrehabilitation was performed in order to improve the patient’s condition.